Determinants of Sovereign Ratings in Emerging Countries: Qualitative Dependent Variables Panel Data Analysis - Kabadayı, Burhan; Çelik, Ahmet Alkan (International Journal of Economics and Financial Issues, 2015)
The aim of this paper is to study determinants of sovereign ratings of emerging countries. The effects of macroeconomic and political variables on the ratings are analyzed by probit and logit panel data analysis. This empirical research determines whether the sovereign ratings of emerging countries are independent of macroeconomic indicators of these countries. It might be vital to know the effects of macroeconomic variables on sovereign rating for politicians, foreign investors, monetary authorities and academicians. Thus, we need efficient and strong models explaining sovereign rating. In the empirical model of the study, qualitative and dependent variable models were used to check the effects of current account deficits, external debts, GDP per capita, real exchange rates, inflations, savings rates and political qualities on sovereign ratings that are exported by three large rating agencies' (S&P, Moodys and Fitch). The results show that macroeconomic political variables affect sovereign ratings. Keywords: Sovereign rating; emerging countries; ordered probit and logit panel data analysis JEL Classifications: C33; G24